O papel da dimensão ambiental na ocupação do MATOPIBA - Junior Ruiz Garcia; José Eustáquio Ribeiro Vieira Filho (Confins)
The demand for natural resources has been accompanied by the economic growth. The expansion of agriculture also has been accompanied by the rise of new frontiers. Faced with the limitation of natural resources, the sector has faced new challenges to increase production. The productive expansion in Brazil has been characterized by the incorporation of the Northeastern Cerrados, a region known as MATOPIBA. This territory is in higher latitudes and subject to a drier and arid climate. In this context, the main objective of the study is to identify the role of environmental constraints in the occupation and expansion of agriculture in the region, precisely to indicate the areas in which public policy investments must focus to mitigate problems and increase productive potential. The search is based on data and information from secondary sources. The treatment of the data was carried out with the aid of the geotechnologies. The results indicate that the region presents a set of environmental and institutional restrictions for the development of agriculture.